Experimental Study on Bond Performance of NC-UHPC Interfaces with Different Roughness and Substrate Strength - Zhang, Boshan; Yu, Jiangjiang; Chen, Weizhen; Liu, Hang; Li, Heng; Guo, Hong (Materials, 2023)
This paper investigates the bond failure performance between precast normal concrete (NC) and cast-in situ ultra-high performance concrete (UHPC), emphasizing the influence of interfacial roughness. The interfacial bonding behavior under tension and under shear was investigated based on 72 groups of pull-off tests and 36 groups of bi-shear tests, considering six different interface treatment methods and two different NC strength levels. The results demonstrate that certain interfacial roughness is essential to gain a reliable bond connection between NC and UHPC. Its enhancement on the tensile bond performance could be described by the positive linear relationship between the mean roughness and the pull-off strength. However, further research is required to determine the characterization method of its influence on the shear bond performance. The higher strength of the base concrete is beneficial to the bond performance. Though this effect is evident in the pull-off tests under tension, the influence on the shear interfacial performance could be offset by that of the interface morphology in the case with high interfacial roughness.